THE ANALYSIS OF PRE AND POST NEGOTIATION OF FRAMING AND PARTNER’S OBJECTIVE ON TRANSFER PRICES - Arief, Sandy; Supriyono, Supriyono (International Journal of Economics, Business, and Entrepreneurship, 2018)
Transfer price negotiations are important to managers as they influence both their own and other divisional profits. These transfer prices are affected by both economic factors (market prices) and behavioral factors including fairness on judgments about negotiated transfer prices. In the current study, we examine whether the impact of accounting information on managers’ transfer price expectations are affected by the way accounting information is framed (either as potential gains or potential losses) and the managers’ perception of the other negotiation partners’ objective (whether their partner’s objective involves high or lowconcern-for-others). These expectations are important as they directly affect the costs and outcomes of negotiations. A controlled laboratory experiment was conducted to test the proposed hypotheses, using a 2 x 2 x 2 between-subjects design. The participants of an experiment were 216 undergraduate accounting students from Faculty of Economics and Business, Soegijapranata Catholic University, Semarang. The results of this study that compared to the mainframe, a loss frame exacerbates managers’ self-serving bias and increases the transfer price expectation gap between buyers and sellers. Further, we found that the negotiation partner’s objective had a significant impact on sellers’ transfer price judgments. This finding also found that the degree of concern for the other party has a significant impact on the judgment, in particular, the transfer price for the seller division.